Promoting Critical Thinking in Anti-Critical Thinking Times: Lessons from COVID Discourse - Burbules, Nicholas (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
We are witnessing what can only be called an anti–critical thinking trend in contemporary society. In this brief essay I want to describe how and why critical thinking is in crisis, and what this means for the promotion of critical thinking as an educational aim. Several of my examples show how this crisis has distorted the public debate over COVID.